On possible Cu doping of Bi2WO6 - Lee, Chnoong Kheng; Sim, Leng Tze; Coats, Alison M.; West, Anthony R. (Royal Society of Chemistry (RSC), 2001)
There has been some controversy over the possibility of doping Bi2WO6 with Cu, in which X-ray powder diffraction (XRD) was used to determine the phase purity of materials. By electron probe microanalysis (EPMA), we find that Cu doping does not result in the formation of single phase material and does not enter the structure of Bi2WO6. Care is needed in using XRD to assess phase purity of materials, especially solid solution phases and also in cases where partial sample volatilisation may have occurred during synthesis.